Working capital management determinants of small and large firms in Malaysia - Mohd Ashhari, Zariyawati; Md Nasir, Annuar; N., Pui-San (Faculty of Economics and Management, Universiti Putra Malaysia, 2016)
Recently, the importance of working capital management has been the subject of intense focus. Firms require efficient working capital management to ensure that their operations remain continuously profitable, which further increases shareholder wealth. The aim of this paper is to provide evidence regarding the determinants of working capital management among small and large firms listed on the Bursa Malaysia stock exchange. Secondary data from 2009-2013 was analyzed using Stata12 software. Results of random effects model demonstrate that firm leverage, firm performance, capital expenditure, operating cash flow, executive compensation and economic conditions are the most significant factors that affect working capital management. In addition, we found that managers of small and large firms make decisions differently in managing working capital.